Concurrent Use of Opioids and Benzodiazepines: Evaluation of Prescription Drug Monitoring by a United States Laboratory. Issue 6 (November 2017) - McClure, Fred Leland; Niles, Justin K.; Kaufman, Harvey W.; Gudin, Jeffrey
Abstract : Objectives: Recently, more than 63% of the 52, 404 drug overdose deaths in the United States involved heroin and opioid pain medications. More than 30% of opioid-related deaths also involved benzodiazepines. Previous studies examining the extent of concurrent opioid and benzodiazepine use have relied on prescription data. To gain fuller insight into the extent of the concurrent use problem, we analyzed opioid and benzodiazepine prescription patterns in the context of drug testing results. Methods: All specimens from patients that were prescribed at least 1 drug and were tested for both opioids and benzodiazepines by a national reference laboratory were included. This resulted in an analytical set of 231, 228 sets of test results from 144, 535 patients with diverse demographic factors being tested in a variety of health care settings. Results: Laboratory test results indicated concurrent use of opioids and benzodiazepines in over 25% of patients. In 52% of test results with evidence of concurrent use, 1 drug class was prescribed and the other was non-prescribed. Nearly 1 in 5 specimens (19%) testing positive for prescribed opioids also tested positive for non-prescribed benzodiazepines. Over 15% of specimens with prescribed benzodiazepines also demonstrated non-prescribed opioid use. Conclusions: The extent of concurrent use of benzodiazepines and opioids, particularly non-prescribed use, suggests the need for more effective clinician assessment and intervention. The results support the Centers for Disease Control and Prevention opioid prescribing guidelines that drug testing occur before and periodically throughout opioid use and suggest that this testing should be extended to patients prescribed benzodiazepines as well. Abstract : Supplemental Digital Content is available in the text